Analisis pemanfaatan aplikasi iHSS oleh pemustaka pada Dinas Perpustakaan dan Kearsipan Kabupaten Hulu Sungai Selatan - Juairiah Juairiah; Laila Rahmawati; Elma Ma'rifah (Pustaka Karya : Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2023)
This study aims to find out how much value the use of the iHSS application has at the Library and Archives Service of Hulu Sungai Selatan Regency. This type of research is descriptive with a quantitative approach. The population of this study was 985 and the samples taken were 91 samples with a tolerable error of 10%. The sampling technique uses the techniques of simple random sampling. Data collection techniques using questionnaires, interviews, observation and documentation. The questionnaire used refers to the Likert scale with a scale of 1-5. Data processing techniques using editing, scoring as well as tabulating and data analysis techniques using descriptive statistical analysis. Data validity and validity techniques used validity and reliability tests with the help of SPSS version 22 and were declared valid and reliable. The results of this study obtained indicators that have the highest average value is Simplicity (Simplicity) is 4.17 and the indicator that has the lowest average value among the others is the indicator Comprehensiveness (Completeness) is 3.80. The results of the evaluation of the iHSS Application Utilization at the Library and Archives Service of Hulu Sungai Selatan District show a total average score of 4.00 which is on a scale of 3.43 – 4.23 and in the high category, which means iHSS application utilization are considered useful.